THE EFFORTS OF LOUISA CLARK’S TO CHANGE LIVES IN THE ME BEFORE YOU MOVIE - Astri Mutia Elshinta Devi; Titis Setyabudi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
The objective of this research were to find out the efforts of Louisa Clark’s to change lives in the Me Before You movie based on striving for superiority and creative self by Alfred Adler. This research use qualitative method to analyze the data. The source data of the research focus on captures from the movie, actions, and sounds or dialogues that describe the efforts of Louisa Clark. The result of this research showed that there are three efforts found, namely getting a job, travelling plans, and living the conveted life.